Identify students’ difficulties in essay writing courses - Nabu, Andiani; Pakaya, Nursela (Journal of English Teaching and Linguistic Issues (JETLI), 2022)
This study aims to determine the students' difficulties in the Essay Writing course. The subjects of this study were fifth semester students of the Department of English Education at IAIN Sultan Amai Gorontalo for the 2019/2020 academic year, totaling 5 students. The method used in this study is a qualitative method with a descriptive design. Data was collected through observation sheets, interviews and documentation. Analysis data is done through data reduction, data presentation, and drawing conclusions. The results showed that there were four difficulties in the Essay Writing course, namely Lack of vocabulary, Lack of grammar mastery, Lack of organization and mechanics mastery in writing. The researcher implies that lecturers must pay attention to students' vocabulary mastery and students' grammatical skills.